Time After Time: Attachment Orientations and Impression Formation in Initial and Longer-Term Team Interactions - Gruda, Dritjon; Berrios, Raul Antonio; Kafetsios, Konstantinos G.; McCleskey, Jim Allen (Frontiers in Psychology, 2022)
If securely attached individuals typically exhibit more desirable attributes, can insecure individuals be perceived positively when working in teams despite their interpersonal disadvantages? In an exploratory study, using both a vignette-based experimental research design (n = 636) and a round-robin study of professionals working on a team task for nine consecutive weeks (k = 648), we examined the evolving impressions of insecurely attached individuals over time. We find that while anxiously attached individuals are perceived more positively in initial interactions, this initial positive effect for anxious attachment disappeared over time as individuals within teams gained more relational knowledge about their team members. We also found a stable and negative effect of avoidant attachment. We discuss possible reasons for the temporal underpinnings of this effect and compare our findings to previous literature.